Moderation Of Patriotism Toward Tax Compliance Aspects - Jaurino, Jaurino; Setiawan, Aris; Febriati, Febriati; Sari, Wilda (LPPM ISNJ Bengkalis, 2024)
This study aimed to test and analyze the effect of taxpayer awareness, e-filing implementation, and tax sanctions on tax compliance with the love of the country as a moderating. This study uses a quantitative method with primary data. The population of this study were taxpayers in Pontianak City and Kubu Raya Regency. The sampling technique used was random sampling. The Hair approach was used to measure the number of samples to obtain a sample of 240 taxpayers. The data collection technique used a questionnaire. The analysis technique used path analysis with a partial least squares structural equation modeling (PLS-SEM) approach based on variance. The study found that taxpayer awareness, e-filing, tax sanctions, and love of the homeland positively affect taxpayer compliance. If taxpayers do not fulfill their responsibilities, they will be punished. Love of the homeland can strengthen the influence of tax sanctions on taxpayer compliance. However, love of the homeland cannot moderate the influence of taxpayer awareness and e-filing on taxpayer compliance. This study can complement the results of previous studies on factors that influence taxpayer compliance. Then, it can help develop a more comprehensive theoretical model and broaden the understanding of taxpayer behavior. This research can help the government make more efficient tax policies and encourage taxpayer compliance.